A framework for interprofessional team collaboration in a hospital setting: Advancing team competencies and behaviours. Issue 2 (March 2022) - McLaney, Elizabeth; Morassaei, Sara; Hughes, Leanne; Davies, Robyn; Campbell, Mikki; Di Prospero, Lisa
Healthcare teams that practice collaboratively enhance the delivery of person-centred care and improve patient and systems outcomes. Many organizations have adopted existing interprofessional frameworks that define the competencies of individual health professionals that are required to meet practice standards and advance interprofessional goals. However, to support the collective efforts of team members to deliver optimal care within complex hospital settings, healthcare organizations may benefit from adopting team-based competencies for interprofessional collaboration. The Sunnybrook framework for interprofessional team collaboration was intentionally created as a set of collective team competencies. The framework was developed using a comprehensive literature search and consensus building by a multi-stakeholder working group and supported by a broad consultation process that included patient representation, organizational development and leadership, and human resources. The six core competencies are actionable and include associated team behaviours that can be easily referenced by teams and widely implemented across the hospital.